IMPLEMENTASI METODE TADRIJ DAN MEDIA SIFALAH DALAM PENINGKATAN HASIL BELAJAR MENYAMBUT SIFAT-SIFAT ALLAH KELAS VII A SMP NEGERI 2 PAKEM BONDOWOSO: SMP NEGERI 2 PAKEM BONDOWOSO - AHNADI AHNADI (Mitra Pendidikan, 2022)
This study aims to improve students' abilities in learning to know the attributes of God. This study used two rounds of classroom action research. Each round consists of four stages: design, activity, observation, and reflection. The research targets were class VIIA students. The data obtained are in the form of test results and observation sheets of teaching and learning activities. Learning in this study applies the Tadrij Method, which is a continuous and gradual training learning model. The results of the study can be concluded that: (1) The application of the tadrij method can improve the ability to recognize God's attributes in class VIIA students of SMP Negeri 2 Pakem in the 2019/2020 academic year. (2) Learning completeness reaches 88%.